Determination of PD-1 expression in peripheral blood cells in patients with endometriosis. (1st February 2021) - Okşaşoğlu, Buğra; Hepokur, Ceylan; Misir, Sema; Yildiz, Çağlar; Sönmez, Gamze; Yanik, Ali
Abstract: In patients with endometriosis, ectopic endometrial tissues can escape from immune system control and survive in other tissues. The pathophysiology of endometriosis is still not fully understood. In this study, we aimed to clarify the pathophysiology of endometriosis, which is thought to be a benign but infiltrative cancer type, which has many similarities with cancer biology by determining PD-1 expression in patients with endometriosis. In this study, n  = 73 cases who underwent surgery or examination at the Obstetrics and Gynecology Clinic of Sivas Cumhuriyet University Faculty of Medicine and diagnosed as endometriosis in the biopsy material taken with the pre-diagnosis of endometriosis constituted the patient group. The control group consisted of n  = 64 healthy subjects without concomitant malignancy or chronic inflammatory disease. Venous whole blood samples were obtained from the study groups. PD-1 and PD-L1 levels were determined by the ELISA method from serum and plasma samples. PD-1 gene expression level was determined by RT-PCR. The PD-1 level was found to be approximately 350 ± 150 ng/L and 45 ± 17 ng/L in endometriosis and control group, respectively. While the PD-L1 level was approximately 760 ± 108 ng/L in the patients, this level was 140 ± 14 ng/L in the controls. According to the RT-PCR results, the expression of the PD-1 gene 10 times higher compared to the controls. Conclusion: The identified increase of PD-1 levels and gene expression in endometriosis groups show that immunotherapy may be used in the treatment of endometriosis.